Refleksi Teologis Kisah Pergumulan Yakub dan Allah dari Bingkai Kaum Pentakostal - Manurung, Kosma; Rakim, Ristan (Sekolah Tinggi Teologi Transformasi Indonesia, 2022)
Abstract: Life is a long process and requires people who live it to keep moving forward. Jacob's life story is a life story that has experienced many ups and downs in it, but near the end of his life, Jacob even had the opportunity to meet and meet the Pharaoh, the ruler of the world at that time. Suspected turning point in Jacob's life that continues to shine into old age is a moment that tells of him struggling with God which is described very nicely in Genesis 32:22-32. This study intends to frame the story of the struggle of Jacob and God in the understanding of the Pentecostals. By using the description and literature review, it is hoped that it will be able to provide a strong and clear picture regarding the review of important events in Jacob's life, the story of the struggle of Jacob and God, as well as the understanding of the Pentecostals in interpreting this story. It is concluded that in Pentecostal understanding the story of the struggle of Jacob and God is interpreted as the importance of personal experience with God, sincerity of heart, learning to see oneself from God's point of view, and answers to prayer.Abstrak: Hidup adalah sebuah proses panjang dan menuntut orang yang menjalaninya untuk terus bergerak maju. Kisah hidup Yakub adalah sebuah kisah kehidupan yang mengalami berbagai proses jatuh bangun didalamnya namun mendekati akhir hidupnya Yakub malah berkesempatan bertemu dan memberkati Firaun penguasa dunia waktu itu. Ditengarai titik balik dalam kehidupan Yakub yang menjadikannya tetap bersinar hingga usia senja adalah sebuat moment yang mengisahkannya bergumul dengan Allah yang digambarkan sangat apik di Kejadian 32:22-32. Penelitian ini bermaksud membingkai kisah pergumulan Yakub dan Allah ini dari pemahaman kaum Pentakostal. Dengan menggunakan deskripsi dan kajian literatur diharapkan mampu memberikan gambaran yang kuat dan jelas terkait ulasan peristiwa penting dalam kehidupan Yakub, kisah pergumulan Yakub dan Allah, serta pemahaman kaum Pentakostal memaknai kisah ini. Disimbulkan bahwa dalam pemahaman kaum Pentakostal kisah pergumulan Yakub dan Allah ini dimaknai sebagai pentingnya pengalaman pribadi dengan Allah, kesunguhan hati, belajar melihat diri dari sudut pandang Tuhan, serta jawaban doa.